2016
DOI: 10.1186/s12944-016-0291-7
|View full text |Cite
|
Sign up to set email alerts
|

The positive association of branched-chain amino acids and metabolic dyslipidemia in Chinese Han population

Abstract: BackgroundIt has been suggested that serum branched-chain amino acids (BCAAs) are associated with the incident, progression and prognostic of type 2 diabetes. However, the role of BCAAs in metabolic dyslipidemia (raised triglycerides (TG) and reduced high-density lipoprotein cholesterol (HDL-C)) remains poorly understood. This study aims to investigate 1) the association of serum BCAAs with total cholesterol (TC), TG, HDL-C and low-density lipoprotein cholesterol (LDL-C) and 2) the association between serum BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 45 publications
7
43
0
Order By: Relevance
“…1 Insulin resistance, as well as β-cell dysfunction, not only contribute to the progression of type 2 diabetes, 2 but are also important precursors of some chronic diseases, including hypertension, metabolic syndrome, dyslipidemia, and cardiovascular disease (CVD). [3][4][5] Insulin resistance has recently received considerable attention, and data reveal that nutritional factors, including food patterns, macronutrients, dietary fiber, and some micronutrients, may be associated with the development of IR. [6][7][8] Branched-chain amino acids (BCAAs), including leucine, isoleucine, and valine, are essential amino acids 9 frequently found in dietary protein, accounting for up to 15%-20% of protein intake, that have direct and indirect metabolic effects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1 Insulin resistance, as well as β-cell dysfunction, not only contribute to the progression of type 2 diabetes, 2 but are also important precursors of some chronic diseases, including hypertension, metabolic syndrome, dyslipidemia, and cardiovascular disease (CVD). [3][4][5] Insulin resistance has recently received considerable attention, and data reveal that nutritional factors, including food patterns, macronutrients, dietary fiber, and some micronutrients, may be associated with the development of IR. [6][7][8] Branched-chain amino acids (BCAAs), including leucine, isoleucine, and valine, are essential amino acids 9 frequently found in dietary protein, accounting for up to 15%-20% of protein intake, that have direct and indirect metabolic effects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 A cross-sectional study by Yang et al revealed that increased total BCAA (T-BCAA) levels were associated with not only elevated TG levels but also reduced HDL-C levels and MD. 7 However, the relationship between individual BCAAs and reduced HDL-C levels was only reported in individuals with impaired glucose tolerance, and thus it remains unclear whether such an association exists in individuals without diabetes or impaired glucose tolerance. Regarding the relationship between BCAAs and LDL-C, Halama et al 8 reported that the by-products of leucine (Leu) degradation could serve as a substrate for cholesterol biosynthesis in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies found no correlation between serum BCAA and LDL-C levels. 7,9 To date, there is no consensus regarding the potential association between BCAAs and elevated LDL-C levels. Hence, further research is warranted to clarify the connection between BCAAs and dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Some case‐control studies in Chinese populations also found correlations between certain metabolite signatures (including amino acids, acylcarnitines, lipids, organic acids and sugar metabolites) and obesity, prediabetes, T2D, diabetic complications, and CVD . In addition, in some cross‐sectional studies, circulating BCAAs were observed to be correlated with the risk of dyslipidemia, metabolic syndrome (MetS), and coronary artery disease (CAD) in Chinese subjects . However, these studies usually had a small sample size, and only a few studies investigated longitudinal associations of these biomarkers.…”
Section: Studies Of Metabolomics In Chinese Populationsmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27] In addition, in some cross-sectional studies, circulating BCAAs were observed to be correlated with the risk of dyslipidemia, metabolic syndrome (MetS), and coronary artery disease (CAD) in Chinese subjects. [28][29][30][31] However, these studies usually had a small sample size, and only a few studies investigated longitudinal associations of these biomarkers. In a recent prospective cohort study, a positive association was reported in 213 Chinese subjects among BCAAs and AAAs with future risk of T2D.…”
Section: Application Of Metabolomics To Disease-related Risksmentioning
confidence: 99%